USE OF VISUAL MODELING IN FORMING PROFESSIONAL COMPETENCE OF STUDENTS OF THE SPECIALIZATION USE OF HYDROTECHNIC INSTALLATIONS AND PUMPING STATIONS - Shaynazarov Ravshan Mamayusubovich (The Conference Hub, 2025)
This article deals with the analysis of the phenomenon of the model in pedagogical research. According to the definitions given in some dictionaries and reference books, the model is understood as an abstract representation of some kind of reality. Models can be of various types. In the context of this study, the main attention is paid to the model. It is observed that modeling is becoming one of the relevant methods of scientific and pedagogical research at the present time.
Keywords: 3D technologies, distance learning, graphic visualization of electronic educational publications, visualization graphic visualization method, didactic features, principles of development of electronic educational publications, etc.